2015
DOI: 10.1111/head.12516
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Block for the Treatment of Headaches and Cranial Neuralgias – A Practical Approach

Abstract: The nerve block can be used in primary (migraine, cluster headache, and nummular headache) and secondary headaches (cervicogenic headache and headache attributed to craniotomy), as well in cranial neuralgias (trigeminal neuropathies, glossopharyngeal and occipital neuralgias). In some of them this procedure is necessary for both diagnosis and treatment, while in others it is an adjuvant treatment. The block of the greater occipital nerve with an anesthetic and corticosteroid compound has proved to be effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 80 publications
(195 reference statements)
1
78
0
10
Order By: Relevance
“…I also argue that if a nerve is truly being compressed, it would likely manifest as a cranial neuralgia. If Dr. de Ru challenges that nerve blocks only work via peripheral mechanisms, how is it possible that nerve blocks can be useful for the treatment of primary headache disorders (migraine, cluster headache, and nummular headache) in addition to cranial neuralgias (glossopharyngeal and occipital neuralgia)? BTX injections and nerve blocks may be useful screening tools, but the results should not be taken in isolation as grounds to proceed with surgery.…”
Section: Dr Mathew's Commentsmentioning
confidence: 99%
“…I also argue that if a nerve is truly being compressed, it would likely manifest as a cranial neuralgia. If Dr. de Ru challenges that nerve blocks only work via peripheral mechanisms, how is it possible that nerve blocks can be useful for the treatment of primary headache disorders (migraine, cluster headache, and nummular headache) in addition to cranial neuralgias (glossopharyngeal and occipital neuralgia)? BTX injections and nerve blocks may be useful screening tools, but the results should not be taken in isolation as grounds to proceed with surgery.…”
Section: Dr Mathew's Commentsmentioning
confidence: 99%
“…[7,8] Based on this view, an appropriate therapeutic method directed at cervical nociceptive structures offers benefit for CEHs. After evaluating the upper cervical nerve root and facet joints, [9,10] the role of degenerative cervical discs in CEHs was noticed. [11,12] Since surprising headache relief after standard neck surgery for myelopathy or radicular shoulder-arm syndrome was previously reported, [11,12] a positive association between CEHs and open cervical surgery has been indicated.…”
Section: Introductionmentioning
confidence: 99%
“…When the greater occipital nerve, lesser occipital nerve, or auriculotemporal nerve is painful at palpation, they suggest to block the nerve(s) with a solution of lidocaine and dexamethasone. If supraorbital, infraorbital, supratrochlear, or infratrochlear nerves are painful, they are blocked only with lidocaine due to aesthetic issues (application of corticosteroids on the face or forehead is linked with skin atrophy, hyper‐ or hypopigmentation, and hair loss) …”
mentioning
confidence: 99%
“…On the other hand, in relation to the treatment of headache attributed to craniotomy, Dach et al suggest amitriptyline and blockade of all painful points found in the scar.…”
mentioning
confidence: 99%
See 1 more Smart Citation